TOXIC EFFECTS OF LARGE DOSE OF QUASSIN IN NORMAL AND DEPRIVED MICROFLORA RAT GROUPS - A.Abbas , Duraid; Al—Shaha,, O.M.S. (The Iraqi Journal of Veterinary Medicine, 2021)
Eighteen rats were divided into three equal groups. The ﬁrst group was closed orally with quassin, the second group was dosed with quassin after the gut ﬂora were suppressed by diﬁerent antibiotics, and the third group was served as a control. Food intake, water intake, and change in body weight were measured daily before dosing, during two weeks of dosing, and during one week after stopping dosing. Two eats from each group were killed at the end of each week, and stomach, liver, and kidney were collected for histopathologic examination.The results show a signiﬁcant decline in daily food intake and daily change in body weight, and a signiﬁcant increase in daily water intake in both dosed groups during the dosing period. Microscopic lesions were seen in the kidneys of both dosed rats group killed at the end of first and second week